Exploring Cross-Cultural Perspectives on AI Education: Insights from Teachers in Nigeria and the USA - Adejoro, Cornelius O; Anuyah, Oghenemaro; Raza, Ali; Badillo-Urquiola, Karla; Yeh, Tom (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
With artificial intelligence (AI) becoming more present in ed-ucation globally, it is essential to consider how cultural con-texts shape teachers’ perspectives, an understanding that sup-ports more inclusive and sustainable learning systems. Thisstudy draws on the African philosophy of Ubuntu to frameour cross-cultural investigation of how children conceptu-alize AI through the lens of their teachers. We conductedsemi-structured interviews with twelve middle school teach-ers in Nigeria and the United States, asking them to interpretAI-themed essays written by students. These teacher reflec-tions revealed differing educational priorities, cultural val-ues, and infrastructural realities: U.S. educators’ interpreta-tions centered on personal development and future careers,while Nigerian teachers highlighted students’ focus on fam-ily, community well-being, and practical societal challenges.Nigerian participants also pointed to the need for improvedinfrastructure (e.g., electricity, internet), broader AI literacy,and education policies that reflect local needs. Our findings il-lustrate how culturally grounded worldviews, such as Ubuntu,shape interpretations of AI and its role in society, and sug-gest that AI education is never culturally neutral. We arguethat AI literacy initiatives must be designed not only to teachtechnical skills but also to support educational sustainability,defined here as inclusive, resilient, and culturally responsivelearning systems capable of evolving within diverse contexts.We offer actionable recommendations for the HCI commu-nity to co-design AI education tools that foreground collec-tive well-being, foster global digital citizenship, and reduceepistemic exclusion in the development of future technolo-gies.